2016
DOI: 10.1097/qad.0000000000001244
|View full text |Cite
|
Sign up to set email alerts
|

Differences in virologic and immunologic response to antiretroviral therapy among HIV-1-infected infants and children

Abstract: Background Virologic and immunologic responses to antiretroviral treatment (ART) in infants may differ from older children due to immunologic, clinical or epidemiologic characteristics. Methods Longitudinal ART responses were modeled and compared in HIV-infected infants and children enrolled in cohorts in Nairobi, Kenya. Participants were enrolled soon after HIV diagnosis, started on ART, and followed for two years. Viral load decline was compared between infant and child cohorts using a nonlinear mixed effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
4
26
1
Order By: Relevance
“…Although we did not find that age was a significant predictor of VS in multivariable models adjusted for clinical characteristics at ART initiation including VL, previous studies have found associations between younger age and lower incidence of suppression . Children with advanced disease at ART initiation take longer and are less likely to achieve VS; they are also at risk for having inadequate immune response to treatment .…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Although we did not find that age was a significant predictor of VS in multivariable models adjusted for clinical characteristics at ART initiation including VL, previous studies have found associations between younger age and lower incidence of suppression . Children with advanced disease at ART initiation take longer and are less likely to achieve VS; they are also at risk for having inadequate immune response to treatment .…”
Section: Discussioncontrasting
confidence: 93%
“…Among infants starting ART at a median age of 5.9 months in pooled data from Southern Africa, only 28% and 56% achieved VS <400 copies/mL at six and twelve months . In our cohort, younger children had significantly higher VL at ART initiation compared to older children (61% of children <12 months had VL >1 million copies compared to 10% of six to twelve year olds) which has also been observed in other studies . In addition to higher VL, younger children may face greater adherence challenges as a result of medication syrups which can be difficult to administer and are highly unpalatable .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A range of factors can influence adherence and viral suppression for children including the child's age, familial and socio-economic environment, stigma, disclosure, and the physical and mental health status of children and caregivers [3,10,54,55]. Consistent with prior studies, we found that older child age was protective against viral non-suppression compared to child age ≤2 years [56][57][58]. This could reflect behavioural changes during childhood such as younger children refusing to take medications or the positive effects of HIV disclosure to older children, the effect of ART dosing frequency (i.e.…”
Section: Discussionsupporting
confidence: 88%